2016
DOI: 10.3389/fphar.2016.00059
|View full text |Cite
|
Sign up to set email alerts
|

Tinospora crispa (L.) Hook. f. & Thomson: A Review of Its Ethnobotanical, Phytochemical, and Pharmacological Aspects

Abstract: Tinospora crispa (L.) Hook. f. & Thomson (Menispermaceae), found in the rainforests or mixed deciduous forests in Asia and Africa, is used in traditional medicines to treat numerous health conditions. This review summarizes the up-to-date reports about the ethnobotany, phytochemistry, pharmacological activities, toxicology, and clinical trials of the plant. It also provides critical assessment about the present knowledge of the plant which could contribute toward improving its prospect as a source of lead mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
130
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(141 citation statements)
references
References 52 publications
2
130
0
9
Order By: Relevance
“…Higenamine (1‐[(4‐Hydroxyphenyl)methyl]‐1,2,3,4‐tetrahydroisoquinoline‐6,7‐diol; HG), also known as dl‐demethylcoclaurine or norcoclaurine, is a benzyl isoquinoline alkaloid. It is widely found in Chinese medicinal materials as well as traditional food materials and additives including aconite roots, Tinospora crispa , Nandina domestica , Gnetum parvifolium , Asarum herb, and Chinese prickly ash . HG was extracted from aconite roots by Kosuge et al in 1978 for the first time .…”
Section: Introductionmentioning
confidence: 99%
“…Higenamine (1‐[(4‐Hydroxyphenyl)methyl]‐1,2,3,4‐tetrahydroisoquinoline‐6,7‐diol; HG), also known as dl‐demethylcoclaurine or norcoclaurine, is a benzyl isoquinoline alkaloid. It is widely found in Chinese medicinal materials as well as traditional food materials and additives including aconite roots, Tinospora crispa , Nandina domestica , Gnetum parvifolium , Asarum herb, and Chinese prickly ash . HG was extracted from aconite roots by Kosuge et al in 1978 for the first time .…”
Section: Introductionmentioning
confidence: 99%
“…Higenamine stimulates beta‐adrenergic receptors (β‐AR)and is considered as an effective anti‐obesity agent . Higenamine is very popular in Chinese medicine and there are numerous papers devoted to its use …”
Section: Introductionmentioning
confidence: 99%
“…3 Higenamine is very popular in Chinese medicine and there are numerous papers devoted to its use. [4][5][6][7][8][9] The structure of higenamine is presented in Figure 1. Higenamine is a chiral compound with 1 asymmetric carbon.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that tinospora extract has antiinflammatory, antioxidant, and antiparasitic activities, which are mainly caused by phenolics, flavonoids, and alkaloids in all parts of the plant, such as leaves, fruits, seeds, roots, and bark. (5,17) In this study the sample of tinospora stem extract tested on TLC showed a content of total phenolics of 43.34% and total flavonoids of 74.26%, which are high for tinospora and represent its antiinflammatory and antioxidant properties. The antioxidant test conducted by Ibrahim et al (13) showed that a methanolic extract of T. crispa had The excellent anti-inflammatory activity of berberine that has been observed in vitro and in vivo showed decreases in pro-inflammatory cytokines in the acute phase.…”
Section: Discussionmentioning
confidence: 99%
“…tinocrisposide, and several alkaloids such as aporphine, berberine and palmatine. (5) In a study of 10 Malaysian medicinal plants, using methanol extracts at concentratiosn of 0.03 µg/ml, T. crispa stem extract showed the highest in vitro antiplasmodial activity to P. falciparum at 90% growth inhibition. (6) Berberine and palmatine significantly inhibit the activation of NFκB and decrease the expression of ICAM-1 and transforming growth factor-beta 1 (TGF-β1) in mesangial cells of rats with diabetic nephropathy, while berberine also inhibits inducible nitric oxide synthase (iNOS) expression.…”
Section: Introductionmentioning
confidence: 99%